Pavlov's dogs and Schrödinger's cat : scenes from the living laboratory - Harré, Rom (OUP E-Books., 2009)
From the sheep, dog, and cockerel that were sent aloft in Montgolfier's balloon to test the air over Paris, to the famous clone Dolly the Sheep and the Darwinian finches of the Galapagos, Pavlov's Dogs and Schrodinger's Cat offers a look at the use of plants and animals--including humans--in scientific experiments. Rom Harre provides a fresh perspective on research, setting aside moral reflection to simply examine the history of how and why living creatures have been used for the purposes of discovery. From Gregor Mendel's use of pea plants to explore heredity, to Barry Marshall's used of himself as the experimental animal in his helicobacter experiments (he survived) and even the use of an imaginary cat in Schrodinger's famous thought experiment, the reader encounters a new perspective on scientific work.